Posterior Cerebral Infarction following Loss of Guide Wire. (8th December 2013) - Bugnicourt, Jean-Marc; Belhomme, Denis; Bonnaire, Bruno; Constans, Jean-Marc; Manaouil, Cécile
Abstract : Stroke after internal jugular venous cannulation typically leads to acute carotid or vertebral arteries injury and cerebral ischemia. We report the first case of delayed posterior cerebral infarction following loss of guide wire after left internal jugular venous cannulation in a 46-year-old woman with a history of inflammatory bowel disease. Our observation highlights that loss of an intravascular guide wire can be a cause of ischemic stroke in patients undergoing central venous catheterization.